SEARCH OF NEW SYNTHETIC INHIBITORS OF TYROSINASE - Shesterenko, Yu.; Romanovska, I.; Sevastyanov, O.; Karpenko, A.; Zanoza, S. (Вісник Одеського національного університету. Хімія, 2017)
Melanin pigmentation of skin plays the most important role in the protection of organism against UV-irradiation, but the excessive accumulation of melanin brings to toxic melanodermia, melasma, lentigo and other skin lesions. Tyrosinase is the key enzyme of skin melanin pigment biosynthesis. In spite of certain progress in investigation of natural and synthetic tyrosinase inhibitors, actuality of such studies is of a high level, because the existing inhibitors are in some cases unstable, expensive, toxic, requires complex methods of synthesis or isolation from natural sources. The aim of the work is screening of new tyrosinase inhibitors, using the enzyme, isolated from Agaricus bisporus. Tyrosinase was isolated from Agaricus bisporus mushrooms by a modified method. It was found, that the introduction of polyethylene glycol 4000 in the extraction process promotes 3-fold reduction of polyphenol content, which leads to increase purity of enzyme with an increase in its activity by 25%. A search for new tyrosinase inhibitors among a wide range of compounds, including derivatives of 3-chloro-1,4-naphthoquinone, isatin, 3-hydroxy-2-naphthoic acid, etc was conducted. The studied substances did not displayed inhibitory effect at concentration of 0,1-0,5 mmol/dm3. It is known, that the natural substrate of mushroom tyrosinase is 1,8-dihydroxynaphthalene, thus it was supposed that the 2,7-dihydroxynaphthalene may be prospective inhibitor of enzyme activity. It was shown, that the concentration of half-maximal inhibition of tyrosinase monophenolase activity by 2,7-dihydroxynaphthalene is close to that of kojic acid – classic inhibitor of melanogenesis. It was found, that 2,7-dihydroxynaphthalene exerts inhibitory action only on monophenolase activity of tyrosinase in contrast to kojic acid, which inhibits both monophenolase and diphenolase enzyme activity.